KARAKTERISTIK INDIVIDU YANG MELAKUKAN PEMERIKSAAN TES HIV DI POLI VOLUNTARY COUNSELING AND TESTING (VCT) RSUD PROF. DR. SOEKANDAR KABUPATEN MOJOKERTO - Asnaningsih, Ambar; Maulida rizkiani, Eka (JURNAL KEPERAWATAN BINA SEHAT, 2016)
ABSTRACTIncreased incidence of HIV is rapidly increasing, especially in Indonesian society, with the increasing information and prevention of the disease, so a lot of people who are aware to check the condition of keksehatannya. This study aims to investigate the characteristics of the individual performing the examination of HIV testing in poly voluntary counseling and testing (VCT). The study design used is descriptive. The population in this study are all visitors inspecting HIV testing in Poli Voluntary Counseling and Testing (VCT) dr. SoekandarMojokerto numbering 20 people. Samples are some individuals who do a HIV test examination in Poli Voluntary Counseling and Testing (VCT) dr. SoekandarMojokerto regency of 20 people using Consecutive sampling techniques. Variables in this research that the characteristics of the individual performing the examination HIV test data collection using research instruments in the form of Check List and questionnaires. Data processing and analysis using the tabulation and then presented in a frequency distribution table. The study of female respondents as many as 11 respondents (55%), respondents aged 26-35 early adulthood as much as 6 respondents (30.0%), the majority of respondents by education high school educated many as 13 respondents (65.0%), respondents by job mostly jobs are at risk of HIV as much as 11 respondents (55.0%), and respondents by more than half knowledgeable knowledge both as much as 11 respondents (55.0%). Expected Health Care Agencies can disseminate to the public by providing counseling in order to increase the number of visits by high risk of HIV and AIDS on the VCT services so that HIV and AIDS can be detected as early as possible.Keywords: Characteristics, HIV, HIV Testing Inspection.